Crop establishment technologies for lowland rice cultivation in Bangladesh: hand seeding vs. machine seeding - Islam, Md. Syedul; Ahmad, Desa (Universiti Putra Malaysia Press, 2010)
Experiments were conducted to determine the field and economic performances of machines and techniques for crop establishment in lowland paddy in Bangladesh. In machine seeded field, the crops were grown in rows to allow the operation of rotary type weeder for weed control. In hand broadcasted field, crops were not arranged in rows and weed control operation was therefore done through traditional means. Results obtained showed that the effect of rice seeding techniques, using pre-germinated rice seed of BR-1 variety on the effective field capacity, was highly significant. The work rate of hand broadcasting was found to be one to one and a half times faster than that of seeding by manually driven drum type row seeder. Field efficiency of hand broadcasting was about 90 percent, and this was found to be significantly higher than those of machine seeding which ranged from 70-80 percent at both seed rates, since no time was lost in turning. BRRI modified drum type row seeder, with a seeding rate of 60 kg/ha, was shown to be better for an optimum crop yield. Based on partial budget analysis, a farmer can save about US$53.34 per hectare in a year using the BRRI modified drum type row seeder, followed by a rotary weeder as compared to hand seeding, followed by hand weeding.